STRATEGI POSITIONING MEREK CHISUM BERDASARKAN PERSEPSI KONSUMEN DI WILAYAH PERKOTAAN JABODETABEK - Cheryn Maylinda; Yunara Marselly; Apriliana Nur Fadillah; Zahra Fitri Nurhasanah; Stephanny Lianardo (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze Chisum’s brand position in the contemporary snack market by comparing it against two main competitors, Shimmy and Yumchi, based on the perceptions of young customers in the Greater Jakarta area. The research method uses a descriptive-comparative quantitative approach with discriminant analysis. Data was obtained through questionnaires distributed to 45 respondents aged 18-35 who had tried all three brands. The assessment was conducted on 10 main attributes, such as Characteristics, Trend, Clarity, Practicality, Personality, and Suitability. The analysis showed that Shimmy excelled in visual differentiation and trend identity, while Yumchi stood out in practicality and relevance to modern lifestyles. Meanwhile, Chisum is in a neutral position, thus requiring a brand repositioning strategy through strengthening visual identity, digital storytelling, packaging innovation, and more precise market segmentation.